Plastid phylogenomics clarifies broad-level relationships in Bulbophyllum (Orchidaceae) and provides insights into range evolution of Australasian section Adelopetalum - Simpson, Lalita; Clements, Mark A.; Orel, Harvey K.; Crayn, Darren M.; Nargar, Katharina (Frontiers in Plant Science, 2024)
The hyper diverse orchid genus Bulbophyllum is the second largest genus of flowering plants and exhibits a pantropical distribution with a center of diversity in tropical Asia. The only Bulbophyllum section with a center of diversity in Australasia is sect. Adelopetalum. However, phylogenetic placement, interspecific relationships, and spatio-temporal evolution of the section have remained largely unclear. To infer broad-level relationships within Bulbophyllum and interspecific relationships within sect. Adelopetalum, a genome skimming dataset was generated for 89 samples, yielding 70 plastid coding regions and the nuclear ribosomal DNA cistron. For 18 additional samples, Sanger data from two plastid loci (matK, ycf1) and nuclear ITS were added using a supermatrix approach. The study provided new insights into broad-level relationships in Bulbophyllum, including phylogenetic evidence for the non-monophyly of sections Beccariana, Brachyantha, Brachypus, Cirrhopetaloides, Cirrhopetalum, Desmosanthes, Minutissima, Oxysepala, Polymeres and Sestochilos. Section Adelopetalum and sect. Minutissima s.s. formed a highly supported clade that was resolved in a sister group position to the remainder of the genus. Divergence time estimations based on a relaxed molecular clock model placed the origin of Bulbophyllum in the early Oligocene (ca. 33.2 Ma) and of sect. Adelopetalum in the late Oligocene (ca. 23.6 Ma). Ancestral range estimations based on a BAYAREALIKE model identified the Australian continent as the ancestral 2 This is a provisional file, not the final typeset article area of sect. Adelopetalum. The section underwent crown diversification during the mid-Miocene to the late Pleistocene, predominantly in continental Australia. At least two independent long-distance dispersal events were inferred eastwards from the Australian continent to New Zealand, and New Caledonia from the early Pliocene onwards, likely mediated by the predominantly westerly winds of the southern hemisphere. Retraction and fragmentation of eastern Australian rainforests from the early Miocene onwards are discussed as likely drivers of lineage divergence within sect. Adelopetalum, facilitating allopatric speciation.